Mapping the Parenting Style: A Child-Perspective Study at Darul Hikmah Islamic Full-Day Elementary School - Atikoh, Nur; Kim Thi My Nguyen (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to identify the predominant parenting styles among Grade VI students at MI Darul Hikmah Full Day School in Cirebon City, Indonesia. Employing a quantitative descriptive approach, the research utilized a structured questionnaire as the primary data collection instrument, distributed to 34 Grade VI students enrolled at the institution. The findings revealed that most respondents (59%) perceived their parental upbringing to align with the "good" category, characterized by supportive and responsive parenting practices. Meanwhile, 41% of students reported parenting styles falling within the "moderate" category, suggesting room for improvement in consistency or emotional engagement. These results underscore the prevalence of positive parenting approaches within the sample while highlighting opportunities for further enhancement. The implications of this study emphasize the need for collaborative efforts between parents and educational institutions to reinforce constructive parenting strategies, particularly in a Full Day School environment where extended school hours necessitate holistic child development support. Recommendations include targeted parental workshops, school-led guidance programs, and ongoing assessments to foster adaptive parenting practices that align with students' academic, social, and emotional needs. This research contributes to the broader discourse on family-school partnerships in optimizing student well-being and developmental outcomes.